The Impersonal: Superadditive Cosmology - Dimitrova, Zornitsa (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
This article positions the concept of the event within a cosmology that affirms its status as an underlying liminality that precedes being yet is additive to the processes that constitute ontological regions. Across a number of event theories, the article shows how the event is systematically defined as an impassive extra-ontological entity that is external in its relation to being yet conditions its emergence.